Rheological behavior of engineered cementitions composites reinforced with PVA fibers. - França, Marylinda Santos de (2018)
The rheological behavior analysis of Engineered Cementitious Composites (ECC) is key to understand how the different preparation techniques affect the composite mechanical performance. However, the rheological assessment of reinforced materials becomes more complex since fibers usually cause flow disturbances not found in nonreinforced cementitious materials. Besides that, simple workability measurement techniques are not able to fully understand the composite behavior in the fresh state creating the need for more precise techniques to be employed. The main objectives of this study were to evaluate the ECC rheological behavior using different rheometer devices (Vane system and Ball measuring system) and investigate the influence of mixing processes on the fiber homogenization and rheological behavior. Additionally to this, a link between rheological behavior and mechanical performance was investigated. In the end, the ball measuring system revealed to be more efficient than the vane system when evaluating the composite rheological behavior. In addition, the mixing process influenced the rheological behavior of PVA-ECC especially regarding the moment which fibers are added. Fiber addition after mortar mixture improved fibers homogenization and reduced mixing energy by around 8%. Moreover, a correlation between rheological and mechanical properties showed that a 2-times variation in either yield stress or viscosity can lead to a variation of more than 50% in flexural strength without significantly affecting the composite compressive strength. It was also found that the lower the composite yield stress and viscosity the higher was its ultimate strain. To conclude, all those parameters contributed to understand the composite rheological behavior and globally optimize its performance.